Lobectomy vs total thyroidectomy for unilateral papillary thyroid carcinoma with ipsilateral cervical lymph node metastasis - Zhang, Shijia; Zhou, Kehui; Wang, Jinyu; Zhao, Ming; Mao, Xiaochun; Shang, Jinbiao; Lan, Xiabin (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to compare the prognosis of unilateral papillary thyroid carcinoma(PTC) patients with ipsilateral cervical lymph node metastasis(IC-LNM) under the treatment of unilateral lobectomy(uLT) vs total thyroidectomy(TT) in order to find out the optimal surgery for these patients without other clinical risk characteristics.MethodsPTC patients at Zhejiang Cancer Hospital between 2012 and 2022 were retrospectively reviewed. Additionally, a propensity score matching(PSM) was performed on patients treated with uLT or TT. Recurrence-free survival(RFS), overall survival(OS), hospitalization costs, postoperative complications, and other clinical characteristics were analyzed between the two groups.ResultsUltimately, 682 unilateral PTC patients with IC-LNM were available in the study. After PSM with possible prognostic factors(such as gender, age, primary tumor size, multifocality, extrathyroidal invasion, and T-stage), 225 pairs of patients were available. With a median of 81(5-154) months follow-up, 22 patients(9.8%) in the uLT and 12(5.3%) in the TT recurred. There were no significant differences in 5-year RFS and 5-year OS between uLT and TT groups. However, TT group was significantly correlated with higher risk of transient and permanent hypoparathyroidism, higher levothyroxine doses, longer hospital stays, and higher hospitalization costs than uLT group(p<0.05).ConclusionsOur study indicated that there were no differences in recurrence and survival between unilateral PTC patients with IC-LNM treated with uLT or TT for the primary tumor. However, uLT group had a lower risk of postoperative complications and a lower hospitalization cost than TT group. Thus, for selected unilateral PTC patients with IC-LNM without other risk features, uLT could be recommended.